Drivers of household water consumption of different socioeconomic classes in selected communities in Metro Manila, Philippines - Ancheta, Maria Anjelica P.; Soriano, Roberto S.; Llaguno, Erickson L. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Metro Manila is the national capital region of the Philippines that has a population of over 12.2 million and has households that belong to different types of socio-economic classes. Since 1999, water supply has become more secured due to the privatization of water utilities in the capital. This study aims to determine if there is a significant relationship between socioeconomic class and household water supply demand in selected communities Metro Manila, which may be used for developing community based policies on water demand management. There is also a need to augment the limited academic literature on urban household water demand in Metro Manila for the past two decades. Based on an extensive review of literature, a survey was conducted in 277 Class DE households in Brgy. Batasan Hills and in 204 Class ABC households in various cities in Metro Manila from October 2016 to February 2017. The significant drivers of consumption were determined using multiple linear regression analysis. Consistent with previous studies, household size accounts for 38% and 40% of the variability in consumption for ABC and DE households, respectively. Results also show that non income factors of socioeconomic class such as the presence of water-intensive appliances and amenities, and the efficiency conservation habits of households were statistically significant drivers of water consumption, accounting for 29% and 3% for ABC and DE households, respectively. Results further show that ABC households consume 35 m3/month almost twice the amount of water relative to DE households with a mean monthly water consumption of 19 m3/month. Comparing the results with a study in 1999 show that the total average water consumption doubled, regardless of socioeconomic class. However, until now, ABC households still consume more than DE households. Furthermore, the results validated that household size is still a major driver, while other potential indicators such as the number of employed members in the household, age, method of vehicle washing, and the breakdown of proxy indicators of income class were found to be statistically significant
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Residential water consumption -- Philippines -- Manila; Water consumption -- Economic aspects